Impact of ozonation and biological post-treatment of municipal wastewater on microbiological quality parameters. Issue 9 (23rd July 2021) - Sauter, Daniel; Stange, Claudia; Schumacher, Vera; Tiehm, Andreas; Gnirss, Regina; Wintgens, Thomas
Abstract : Biological post-treatment after ozonation in tertiary municipal wastewater treatment significantly improves the abatement of several microbiological quality parameters. Abstract : Ozonation is an established process for advanced wastewater treatment, with a dose-dependent degree of disinfection. It is generally followed by biological post-treatment with the main objective of oxidation by-product abatement. However, there is little research on the impact of the combination of ozonation and biological post-treatment on microbiological quality parameters. This long-term study investigated pilot-scale ozonation with six different filtration processes (4 deep-bed filter systems and 2 vertical flow constructed wetlands) as biological post-treatment. A broad spectrum of microbial parameters has been monitored for a comprehensive evaluation of the disinfection performance. While vegetative bacteria ( Escherichia coli and enterococci) were inactivated to a large extent by ozone, spore-forming Clostridium perfringens and viral indicator somatic coliphages exhibited a high ozone tolerance and could only be effectively retained in subsequent filtration steps. Extended hydraulic retention times as well as fine filter materials in post-treatment proved to be beneficial for faecal indicator abatement. In deep-bed filters, coagulant dosing was an additional important factor for the disinfection performance. Post-treatment also played a crucial role in the reduction of the antibiotic resistance gene sul 1 and the indicator genes intl 1 (mobile genetic element) and 16S rRNA (total bacterial number), whereas inactivation of antibiotic resistant bacteria was dominated by the ozonation process. In summary, the combined disinfection mechanisms of ozonation (chemical) and filtration (physical) resulted in an effective abatement of a wider range of microbial parameters than the individual processes. Regrowth during post-treatment has only been observed for the parameters intact cell counts and Pseudomonas aeruginosa with mean concentration increases of 0.5–1 log units.